White Daughter of Empire: A Pilgrim of Justice and Peace Owning White Privilege. Issue 1 (21st January 2020) - Durber, Susan
Abstract: As a white British woman, drawing on a Pilgrim Team Visit to Bangladesh in 2019, I reflect on racism, Empire, and white privilege and on how my eyes have been opened to the history that has shaped me, the wider world, and the Christian faith I have inherited. Through personal memoir, critical reflection on experience, and academic reading, I confront how racism, as a combination of power and prejudice, provides the lens through which I see the world, as a white British woman, and how experience and faith must both challenge and redeem.